Polycistronic Expression of Human Platelet Factor 4 with Heparin-Neutralizing Activity in Escherichia coli - DUAN, Yitao; WANG, Zhe; WU, Wei; FANG, Zhenjiang; HUANG, He (Bioscience, biotechnology, and biochemistry, 2012)
Human platelet factor 4 (hPF4) was evaluated as a clinical alternative to protamine for heparin neutralization, a protector against radiation injury and an anti-neoplastic. To achieve high-level expression of hPF4, expression vectors pET-28a(+)-nf PF4 (n=4, 5, 6) containing n tandem repeats of PF4 were constructed and transformed into the Escherichia coli BL21(DE3) strain. A higher expression level, about 45% of the total proteins (TP), was obtained for E. coli BL21(DE3)/pET28a(+)-nf PF4 (n=4, 5, 6). The purified His-PF4 protein was further identified by cleavage with enterokinase and MS, and its heparin-neutralizing activity was determined by colony formation assay. This study represents a novel approach to large-scale production of PF4 in E. coli, one that might be applied to large-scale production of PF4 protein for possible clinical application. It also provides theoretical points for the expression and purification of other small-molecule peptides.